Ultrafast optical response of Tl2Ba2CuO6+delta - Smith, D; Gay, P; Stevens, C; Wang, D; Wang, J; Ren, Z; Ryan, J (1999)
We present the first measurements of the ultrafast optical response of Tl2Ba2CuO6+delta and show that the optical response is clearly sensitive to the electronic groundstate. In the superconducting state its decay can be interpreted as following the reformation of superconducting pairs and the dynamics of quasiparticles near the nodes in a d-mave gap.